Pityriasis rosea-like rash after COVID-19 vaccination with Oxford-AstraZeneca: a possible trigger? - Eibs Cafrune, Fernando; Resener de Morais, Marina; Bevilaqua, Mariele; de Jesus, Luyze Homem (Clinical and Biomedical Research, 2023)
Scholars around the world have dedicated themselves to developing an effective vaccine against SARS-CoV-2. However, vaccines have produced adverse effects in some patients. We report the case of a 44-year-old man who developed a pruritic papulosquamous rash on the trunk with a characteristic pattern known as Christmas tree after receiving the first dose of the Oxford- AstraZeneca COVID-19 vaccine, similar to pityriasis rosea (PR). He had no previous symptoms of viral infection and tested negative for neutralizing antibodies (enzyme immunoassay) against COVID-19. There are few reports in the literature about the relationship between the onset of cutaneous adverse reactions and the Oxford-AstraZeneca vaccine, therefore, the dissemination of this case is of paramount importance.